BODY SIZE REDUCTION AND TOOTH AGENESIS IN LATE PLEISTOCENE MELES MELES (CARNIVORA, MAMMALIA) FROM INGARANO (SOUTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
In mammals combined factors such as body size reduction and loss of peripheral teeth are often associated with endemism phenomena. This condition is particularly evident in insular contexts where is a complete geographic isolation. During the Pleistocene there have been several glacial stages, which changed the physiognomy of the Italian peninsula strongly influencing the distribution and morphology of mammalian faunas. Several genetic studies have shown that some Southern Italian areas have particular endemic species of small and medium size mammals. During Pleistocene these areas have been characterized by particular climatic/environmental conditions, and are generally called "glacial refugia". They represent geographically isolated areas over time, where the origin of faunas with peculiar features is favoured. In this study, the occurrence of Meles meles from the Late Pleistocene site of Ingarano (Apulia, Southern Italy) is documented for the first time. This taxon is represented only by a partial skull (splancnocranum) that, despite the relative completeness, includes peculiar and well-preserved dental features that could be related to a partial endemic condition. The fossil shows a reduced body size and the agenesis of peripheral teeth, both conditions that are typical of the extant badgers from Crete, Rhodes and Japan. To test this hypothesis, tomographic analysis have been provided to establish the dental agenesis, and, in order to understand the magnitude of the body size reduction, biometric analyses have been carried on. The obtained data have been compared to measures of the extant Eurasian badgers.SHORT NOTE